2010
DOI: 10.1055/s-0030-1261876
|View full text |Cite
|
Sign up to set email alerts
|

Total and Cardiovascular Disease Mortality Predicted by Metabolic Syndrome is Inferior Relative to its Components

Abstract: There was no added predictive value of MetS beyond its individual components with respect to mortality risk. Attention should be redirected to the individual components, particularly visceral obesity and high glucose, to treat each abnormality appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…27 28 32 33 Some argue that in defining MS, we lose rather than gain predictive power for CVD and mortality if MS does not confer any risk beyond that of its individual components, because in defining MS in a dichotomous fashion, requiring the presence of three or more risk factors, we lose predictive information from some risk factors entirely and from others in part. 5 7 Some individual reports, [8][9][10] and meta-analyses 2 34 suggest that the value of MS beyond that of its individual components or traditional risk factors as a predictor of mortality and CVD is modest at best, in contrast to other reports. [12][13][14][15][16][17] However, as Ford 2 suggests, a gradient of risk of adverse outcomes may exist within MS due to other factors not included in the definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 28 32 33 Some argue that in defining MS, we lose rather than gain predictive power for CVD and mortality if MS does not confer any risk beyond that of its individual components, because in defining MS in a dichotomous fashion, requiring the presence of three or more risk factors, we lose predictive information from some risk factors entirely and from others in part. 5 7 Some individual reports, [8][9][10] and meta-analyses 2 34 suggest that the value of MS beyond that of its individual components or traditional risk factors as a predictor of mortality and CVD is modest at best, in contrast to other reports. [12][13][14][15][16][17] However, as Ford 2 suggests, a gradient of risk of adverse outcomes may exist within MS due to other factors not included in the definition.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 Detractors from MS have suggested that its relevance in terms of CVD risk is no greater than the contribution of the individual components. [7][8][9][10][11] Others have suggested that MS contributes significantly to CVD risk after correcting for risk associated with MS components in isolation, and/ or traditional CVD risk factors not included in the definitions of MS (eg, smoking). [12][13][14][15][16][17] Differences in the characteristics of populations studied may account for some of the observed disparity in studies of MS and CVD, and-in particular-many, 8 13 18-23 but not all, 17 24 25 studies have suggested MS may have little or no association with CVD in elderly populations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This is true not only in the general population but also in patients with the syndrome and type 2 diabetes mellitus, where it accounts for up to one-third of CVD in men and approximately half of new cases. 8,9 Yet, this association has been seriously questioned, [10][11][12] so that it appears that this issue is far from being settled clinically and semantically. [13][14][15] This discrepancy of opinions is probably dictated by the complex pathophysiology of the syndrome itself.…”
Section: Introductionmentioning
confidence: 99%
“…However, when we used genetic instruments in subsequent IV analyses to represent lifetime serum testosterone concentrations free of residual confounding or reverse causation, none of these previous associations were proved to be causal. The metabolic syndrome consists of a cluster of cardiometabolic risk factors, including visceral obesity, glucose intolerance, dyslipidaemia and hypertension; which strongly predict subsequent CVD (Sattar et al, 2003) and mortality (Haring et al, 2010c). However, although previous prospective studies showed that low testosterone concentration precede the development of metabolic syndrome (Haring et al, 2009b;Kupelian et al, 2006), reverse causality remains a possibility (Laaksonen et al, 2005), as it remains still unclear whether low testosterone concentrations contributes to or are a very early consequence of mechanisms finally leading to overt metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%